Heterogeneous Bequests and Social Inequalities - Kirill Borissov; Stefano Bosi; Thai Ha-Huy; Mikhail Pakhnin (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study a growth model with two types of agents who are heterogeneous in their degree of family altruism. We prove that every equilibrium path converges to a unique steady state, and study the effect of altruism on the properties of steady-state equilibrium. We show that aggregate income is positively related to both level of altruism and altruism heterogeneity. When altruism heterogeneity is low, income inequality follows an inverse U-shaped pattern relative to the level of altruism, which is consistent with the cross-country Kuznets curve. When altruism heterogeneity is high, income inequality monotonically decreases with the level of altruism. Our results suggest that heterogeneous altruism is an important mechanism linking economic growth and income inequality.
Keywords: D15; D64; E21; O40; 330; economic growth; heterogeneous agents; altruism; bequests; inequality; Kuznets curve